Asian development outlook 2014 update Asia in global value chains (Asian Development Bank, 2014)
Developing Asia is continuing along a stable growth path. Although US policy could still surprise markets the effect on developing Asia would be modest compared to the shock caused in 2013 by anticipated tightening. Demand does not threaten to reignite inflation, as regional economies continue to produce somewhat below capacity. This and benign international commodity prices will keep inflation in developing Asia moderate Many economies in Asia have grown by connecting with global value chains. Strengthening these links could further stimulate expansion of industry and services and create jobs.